Home » Inequalities » Page 2

Tag: Inequalities

Prove some inequalities of sin x

For all x > 0 prove that

    \[ x - \frac{x^3}{6} < \sin x < x. \]


From the first exercise of this section on inequalities, we know \sin x < x for all 0 < x < \frac{\pi}{2}. But since \sin x \leq 1 for all x and 1 < \frac{\pi}{2} we have the inequality on the right immediately,

    \[ \sin x < x \qquad \text{for all } x > 0. \]

For the inequality on the left let

    \[ f(x) = \sin x - x + \frac{x^3}{6}. \]

Then, we’ll consider the first two derivatives of f to show that it is positive for all x > 0.

    \begin{align*}  f'(x) &= \cos x - 1 + \frac{x^2}{2} \\  f''(x) &= -\sin x + x = x - \sin x. \end{align*}

We know from the inequality on the right that \sin x < x for all x > 0. Hence, f''(x) > 0 for all x > 0. Therefore, f'(x) is increasing on the positive real axis. Since

    \[ f'(0) = \cos 0 - 1 + \frac{0^2}{2} = 0 \]

we then have that f'(x) > 0 for all x> 0. Hence, f(x) is increasing on the positive real axis, and since

    \[ f(0) = \sin 0 - 0 + \frac{0^3}{6} = 0 \]

we have that f(x) > 0 for all x >0. Thus, for all x>0,

    \[ \sin x - x + \frac{x^3}{6} > 0 \quad \implies \quad x - \frac{x^3}{6} < \sin x. \qquad \blacksquare \]

Prove inequalities of the log of 1 + 1/x

For x > 0 prove that

    \[ \frac{1}{x + \frac{1}{2}} < \log \left( 1 + \frac{1}{x} \right) < \frac{1}{x}. \]


Before the proof, a picture for this one is probably useful. In the graph below we are going to get the inequality on the right by comparing the area under the graph of \frac{1}{x} from x to x+1 (blue curve) and the area of the rectangle under the blue dashed line from x to x+1. We’ll show that the area of the rectangle is 1/x and the area under the curve is \log \left( 1 + \frac{1}{x} \right).

Rendered by QuickLaTeX.com

Proof. First, we note that

    \[ \log \left( 1 + \frac{1}{x} \right) = \log \left( \frac{x+1}{x} \right) = \log (x+1) - \log x. \]

Furthermore,

    \[ \int_x^{x+1} \frac{1}{t} \, dt = \log (x+1) -  \log x. \]

Therefore we have

    \[ \log \left( 1 + \frac{1}{x} \right) = \int_x^{x+1} \frac{1}{t} \, dt. \]

(In the picture this is the area under the curve between x and x+1.)
Since the function \frac{1}{t} is strictly decreasing on the positive real axis (since it’s derivative is -\frac{1}{t^2} is negative everywhere) we know that for any fixed x> 0 we have \frac{1}{x} > \frac{1}{t} for every t \in (x, x+1). Therefore, by the monotone property of the integral,

    \[ \int_x^{x+1} \frac{1}{t} \, dt < \int_x^{x+1} \frac{1}{x} \, dt = \frac{1}{x} \int_x^{x+1} dt = \frac{1}{x}. \]

(Note the \frac{1}{x} inside the integral is a constant here since we have chosen some fixed x>0. For any fixed x the point \frac{1}{x} is the point on the curve f(x) at the left end of the interval. So, this is saying the integral of the curve \frac{1}{t} from x to x+1 is less than the integral of the rectangle of height \frac{1}{x} from x to x+1.) This gives us the inequality on the right that we wanted,

    \[ \log \left( 1 + \frac{1}{x} \right) < \frac{1}{x}. \]

Now, to prove the inequality on the left we know that x > 0 if and only if \frac{1}{x} > 0. Thus, the given inequality holds for all x>0 if and only if it holds for all \frac{1}{x} > 0. Therefore,

    \[ \frac{1}{x+\frac{1}{2}} < \log \left( 1+ \frac{1}{x} \right) \]

if and only if

    \[ \frac{1}{\frac{1}{x} + \frac{1}{2}} < \log \left( 1 + \frac{1}{1/x} \right) \implies \frac{x}{1+\frac{1}{2} x} < \log (1+x). \]

Now, consider

    \begin{align*}    f(x) &= \log(1+x) - \frac{x}{1+\frac{1}{2}x} \\[9pt]  f'(x) &= \frac{1}{1+x} - \frac{1+\frac{1}{2}x - \frac{1}{2}x}{(1+\frac{1}{2}x)^2} \\[9pt]  &= \frac{1}{1+x} - \frac{1}{1+x+\frac{1}{4}x^2} \\[9pt]  &> 0 \end{align*}

for all x > 0. Therefore, f(x) is increasing on the positive real axis. Since

    \[ f(0) = \log (1+0) - \frac{0}{1+\frac{1}{2}\cdot0} = 0, \]

we have that f(x) > 0 for all x > 0. Hence, we obtain the inequality on the left

    \[ \frac{1}{x+\frac{1}{2}} < \log \left( 1+\frac{1}{x} \right). \qquad \blacksquare\]

Prove the inequality 2x/π < sin x < x for 0 < x < π/2

Prove the inequality

    \[ \frac{2}{\pi}{x} < \sin x < x \qquad \text{for} \quad 0 < x < \frac{\pi}{2}. \]


Proof. Define a function f(x) = x - \sin x. Then, since \cos x < 1 for 0 < x < \frac{\pi}{2} we have

    \[ f'(x) = 1 - \cos x > 0 \qquad \text{for } 0 < x < \frac{\pi}{2}. \]

Since f(0) = 0 and f is increasing on 0 < x < \frac{\pi}{2} (since its derivative is positive) we have

    \[ f(x) > 0 \quad \implies \quad x - \sin x > 0 \quad \implies \quad x > \sin x. \]

For the inequality on the left (which is much more subtle), we want to show

    \[ \frac{2}{\pi}x < \sin x \qquad \text{which implies} \qquad frac{2}{\pi} < \frac{\sin x}{x}. \]

So, we consider the function

    \[ f(x) = \frac{\sin x}{x} \quad \implies \quad f'(x) = \frac{x \cos x - \sin x}{x^2}. \]

We know

    \[ \lim_{x \to 0} f(x) = \lim_{x \to 0} \frac{\sin x}{x} = 1 \]

and

    \[ f \left( \frac{\pi}{2} \right) = \frac{2}{\pi}. \]

Now, if we can show that f(x) is decreasing on the whole interval \left( 0, \frac{\pi}{2} \right) then we will be done (since this would mean f(x) > \frac{2}{\pi} on the whole interval since if it were less than \frac{2}{\pi} somewhere then it would have to increase to get back to \frac{2}{\pi} on the right end of the interval).

To show f(x) is decreasing on the whole interval we will show that its derivative is negative. To that end, define a function

    \[ g(x) = x \cos x - \sin x \]

(This is the numerator in the expression we got for f'(x). Since we know the denominator of that expression is always positive, we are going to show this g(x) is always negative to conclude f'(x) is always negative.) Now, g(0) = 0 and

    \[ g'(x) = \cos x - x \sin x - \cos x = -x \sin x < 0 \]

for 0 < x < \frac{\pi}{2}. Thus, g'(x) is negative, and so g(x) is decreasing. Since g(0) = 0 we then have g(x) is negative on the whole interval. Therefore, f'(x) \leq 0 on the interval. Hence, f(x) is decreasing. Hence, we indeed have

    \[ \frac{\sin x}{x} > \frac{2}{\pi} \quad \implies \quad \sin x > \frac{2}{\pi}x \]

for all x \in \left( 0, \frac{\pi}{2} \right). \qquad \blacksquare

Prove some inequalities of the exponential function

For n \in \mathbb{Z}_{>0} and for x \in \mathbb{R}_{>0} prove the following inequalities,

    \[ \left( 1 + \frac{x}{n} \right)^n < e^x, \qquad e^x < \left( 1 - \frac{x}{n} \right)^{-n}, \]

where we assume x < n in the second inequality. Use this to show

    \[ 2.5 < e < 2.99. \]


Proof. From the previous exercise (Section 6.17, Exercise #41) we know

    \[ e^x > 1 + x \]

for x > 0. But by assumption we have x > 0 and n> 0; hence, \frac{x}{n} > 0. Therefore this inequality must hold for \frac{x}{n}:

    \[ e^{\frac{x}{n}} > 1 + \frac{x}{n} \quad \implies \quad e^x > \left( 1  + \frac{x}{n} \right)^n. \]

Again, by the previous exercise we have

    \[ e^{-x} > 1 - x \]

for x > 0. Since x > 0 and n > 0 this implies \frac{x}{n} > 0. Therefore,

    \begin{align*}    e^{-\frac{x}{n}} > 1 - \frac{x}{n} && \implies && e^{-x} > \left( 1 - \frac{x}{n} \right)^n \\  && \implies && e^x < \left( 1 - \frac{x}{n} \right)^{-n}. \qquad \blacksquare \end{align*}

Letting n = 6, we have

    \[ \left( 1 + \frac{1}{6} \right)^6 = 2.52 < e < \left(1 - \frac{1}{6} \right)^{-6} = 2.99. \]

Prove some inequalities using the function ex-1-x

  1. Define a function:

        \[ f(x) = e^x - 1 - x \qquad \text{for all } x \in \mathbb{R}. \]

    Prove that f'(x) \geq 0 for all x \geq 0 and f'(x) \leq 0 for all x \leq 0. Prove the following inequalities are valid for all x > 0,

        \[ e^x > 1 + x, \qquad e^{-x} > 1 -x. \]

  2. Using integration and part (a) prove

        \[ e^x > 1 + x + \frac{x^2}{2!}, \qquad e^{-x} < 1 - x + \frac{x^2}{2!}. \]

  3. Using integration and part (a) prove

        \[ e^x > 1 + x + \frac{x^2}{2!} + \frac{x^3}{3!}, \qquad e^{-x} > 1 - x + \frac{x^2}{2!} - \frac{x^3}{3!}. \]

  4. State and prove a generalization of the inequalities above.

  1. First, we take the derivative of f(x),

        \[ f'(x) = e^x - 1 \quad \implies \quad f'(0) = 0. \]

    Since e^x - 1 is strictly increasing everywhere (since f''(x) = e^x > 0 for all x) we have f'(x) \geq 0 for x \geq 0 and f'(x) \leq 0 for x \leq 0. Thus, f(x) has a minimum at x = 0 and f(0) = 0 so f(x) > 0 for all x \neq 0. Therefore, f(x) > 0 when x > 0; hence,

        \[ e^x -1 - x > 0 \quad \implies \quad e^x > 1 + x. \]

    Furthermore, when x < 0 we have

        \[ e^x - 1 - x > 0 \quad \implies \quad e^x > 1 + x. \]

    Therefore, if x > 0 then -x < 0 and so we have

        \[ e^{-x} > 1 - x. \]

  2. Using the inequalities in part (a) we integrate over the interval 0 to x,

        \begin{align*}  e^x > 1 + x && \implies && \int_0^x e^t \, dt > \int_0^x (1+t) \, dt \\  && \implies && e^x - 1> \left(t + \frac{t^2}{2}\right)\Bigr \rvert_0^x + C \\  && \implies && e^x - 1> x + \frac{x^2}{2!} \\  && \implies && e^x > 1 + x + \frac{x^2}{2!} \end{align*}

    For the other inequality we proceed similarly,

        \begin{align*}  e^{-x} > 1 - x && \implies && \int_0^x e^{-t} \, dt &> \int_0^x (1-t) \, dt \\  && \implies && -e^{-x} + 1 &> x - \frac{x^2}{2}\\  && \implies && e^{-x} &< 1 - x + \frac{x^2}{2!}. \qquad \blacksquare  \end{align*}

  3. We use the same strategy as before, starting with the inequalities we established in part (b),

        \begin{align*}  e^x > 1 + x + \frac{x^2}{2!} && \implies && \int_0^x e^t \, dt > \int_0^x \left (1 + t + \frac{t^2}{2!} \right) \, dt \\  && \implies && e^x - 1 > \left( t + \frac{t^2}{2!} + \frac{t^3}{3!}\right)\Bigr \rvert_0^x \\  && \implies && e^x > 1 + x + \frac{x^2}{2!} + \frac{x^3}{3!}. \end{align*}

    Similarly, for the other inequality,

        \begin{align*}  e^{-x} < 1 - x + \frac{x^2}{2!} && \implies && \int_0^x e^{-t} \, dt &< \int_0^x \left( 1 - t + \frac{t^2}{2!} \right) \, dt \\  && \implies && -e^{-x} + 1& < x - \frac{x^2}{2!} + \frac{x^3}{3!} \\  && \implies && e^{-x} &> 1 - x +\frac{x^2}{2!} - \frac{x^3}{3!}. \qquad \blacksquare \end{align*}

  4. Claim: The following general inequalities hold for all x > 0:

        \begin{align*}  e^x &> \sum_{k=0}^n \frac{x^k}{k!} & \text{for all } n \in \mathbb{Z}_{>0} \\ e^{-x} &> \sum_{k=0}^n (-1)^k \frac{x^k}{k!} & \text{for all odd } n \in \mathbb{Z}_{>0} \\ e^{-x} &< \sum_{k=0}^n (-1)^k \frac{x^k}{k!} & \text{for all even } n \in \mathbb{Z}_{>0}. \end{align*}

    Proof. The proof is by induction. We have already established the inequalities for the n = 1 case for all three inequalities. Now, to prove the first inequality assume

        \[ e^x > \sum_{k=0}^n \frac{x^k}{k!} \qquad \text{for some } n \in \mathbb{Z}_{>0}. \]

    Then we have

        \begin{align*}  && \int_0^x e^t \, dt &> \int_0^x \left( \sum_{k=0}^n \frac{t^k}{k!} \right) \, dt \\[9pt]  \implies && e^x - 1 &> \sum_{k=0}^n \int_0^x \frac{t^k}{k!} \, dt &(\text{linearity of integral}) \\[9pt]  \implies && e^x &> 1 + \sum_{k=0}^n \left( \frac{t^{k+1}}{(k+1)!} \right)\Bigr \rvert_0^x \\[9pt]  \implies && e^x &> 1 + \sum_{k=0}^n \frac{x^{k+1}}{(k+1)!} \\[9pt]  \implies && e^x &> 1 + \sum_{k=1}^{n+1} \frac{x^k}{k!} &(\text{Reindexing})\\  \implies && e^x &> \sum_{k=0}^{n+1} \frac{x^k}{k!}. \end{align*}

    This establishes the first inequality. For the second inequality we have proved the case n = 1 already. Assume

        \[ e^{-x} > \sum_{k=0}^n (-1)^k \frac{x^k}{k!} \qquad \text{for some odd } n \in \mathbb{Z}_{>0}. \]

    Since n is odd we may write n = 2m+1 for some nonnegative integer m. We want to show that the inequality must hold for the next odd integer, n+2. We have,

        \begin{align*}  &&\int_0^x e^{-t} \, dt&> \int_0^x \left( \sum_{k=0}^n (-1)^k \frac{t^k}{k!} \right) \, dt \\  \implies && -e^{-x} + 1 &> \sum_{k=0}^n (-1)^k \int_0^x \frac{t^k}{k!} \, dt \\  \implies && -e^{-x} &> -1 + \sum_{k=0}^n (-1)^k \frac{x^{k+1}}{(k+1)!} \\  \implies && e^{-x} &< 1 - \sum_{k=0}^n (-1)^k \frac{x^{k+1}}{(k+1)!} \\  \implies && e^{-x} &< 1 - \sum_{k=1}^{n+1} (-1)^{k-1} \frac{x^k}{k!} \\  \implies && e^{-x} &< 1 + \sum_{k=1}^{n+1} (-1)^k \frac{x^k}{k!} \\  \implies && e^{-x} &< \sum_{k=0}^{n+1} (-1)^k \frac{x^k}{k!} \\ \end{align*}

    We want to show that the inequality holds for n+2 so we integrate both sides again,

        \begin{align*}  && e^{-x} &< \sum_{k=0}^{n+1} (-1)^k \frac{x^k}{k!} \\  \implies && \int_0^x e^{-t} \, dt &< \int_0^x \left( \sum_{k=0}^{n+1} (-1)^k \frac{x^k}{k!} \right) \, dx \\  \implies && -e^{-x} + 1 &< \sum_{k=0}^{n+1} (-1)^k \int_0^x \frac{t^k}{k!} \, dt \\  \implies && -e^{-x} &< -1 + \sum_{k=0}^{n+1} (-1)^k \frac{x^{k+1}}{(k+1)!} + C \\  \implies && -e^{-x} &< -1 + \sum_{k=1}^{n+2} (-1)^{k-1} \frac{x^k}{k!} \\  \implies && e^{-x} &> 1 - \sum_{k=1}^{n+2} (-1)^{k-1} \frac{x^k}{k!} \\  \implies && e^{-x} &> 1 + \sum_{k=1}^{n+2} (-1)^k \frac{x^k}{k!} \\  \implies && e^{-x} &> \sum_{k=0}^{n+2} (-1)^k \frac{x^k}{k!}. \end{align*}

    Hence, if the inequality holds for odd n, then it also holds for the next odd number, n+2. Hence, it holds for all positive, odd integers.
    The exact same induction argument works for all of the even integers (starting with the n = 2 case we proved in part (c)). \qquad \blacksquare